The abyss [videorecording (DVD)] - Cameron, James, 1954-; Hurd, Gale Anne; Harris, Ed, 1950-; Mastrantonio, Mary Elizabeth (20th Century Fox Home Entertainment, 2000)
When a nuclear submarine mysteriously sinks, the Navy commandeers the crew of a civilian deep sea oil rig to help in the rescue operation. This perilous mission becomes a wondrous odyssey into the unknown as forces from the ocean's deepest region begin to make contact with the divers.